2023
DOI: 10.1017/s0890060422000270
|View full text |Cite
|
Sign up to set email alerts
|

Towards the conceptual design of ML-enhanced products: the UX value framework and the CoMLUX design process

Abstract: With the increasing utilization of machine learning (ML) to enhance products’ capabilities, the design research community has begun to explore how to support the conceptual design of ML-enhanced products. However, UX value creation of ML-enhanced products is still challenging because of ML's unique characteristics and numerous complex factors in conceptual design. To help designers create UX value for ML-enhanced products, we developed the UX value framework and the CoMLUX design process. The proposed framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…This thematic collection encompasses a wide range of studies exploring various aspects of applying AI techniques and cognitive science in design. Some studies have focused on how AI can be used to augment and support humans in design (Sun et al, 2023a;Wang et al, 2023), some explored new user cognitive models for design (Tehranchi et al, 2023), while others probed human design cognition using neurophysiological and biometric measures (Hu et al, 2023;Sun et al, 2023b;Yin et al, 2023;Zhang et al, 2023). Additional studies have exploited AI for analyzing design cognitive data (Chiu et al, 2023;Hu et al, 2023;Sun et al, 2023b;Zhang et al, 2023).…”
Section: Applications Of Ai and Cognitive Science In Designmentioning
confidence: 99%
See 2 more Smart Citations
“…This thematic collection encompasses a wide range of studies exploring various aspects of applying AI techniques and cognitive science in design. Some studies have focused on how AI can be used to augment and support humans in design (Sun et al, 2023a;Wang et al, 2023), some explored new user cognitive models for design (Tehranchi et al, 2023), while others probed human design cognition using neurophysiological and biometric measures (Hu et al, 2023;Sun et al, 2023b;Yin et al, 2023;Zhang et al, 2023). Additional studies have exploited AI for analyzing design cognitive data (Chiu et al, 2023;Hu et al, 2023;Sun et al, 2023b;Zhang et al, 2023).…”
Section: Applications Of Ai and Cognitive Science In Designmentioning
confidence: 99%
“…In this thematic collection, Wang et al (2023) assessed the creativity of AI-generated designs by using both human experts and computational techniques, Tehranchi et al (2023) showed the importance of human behavior predictions in computational models for design, and Sun et al (2023a) indicated the inclusion of human designers in ML lifecycles could better support the generation of design solutions. These three studies have shown the significance and potential necessity of integrating human expertise and intelligence into AI design process.…”
Section: Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation